Effectiveness of personal protective measures in reducing pandemic influenza transmission: A systematic review and meta-analysis - Saunders-Hastings, Patrick; Crispo, James A.G.; Sikora, Lindsey; Krewski, Daniel (Université d'Ottawa | University of Ottawa, 2017)
The goal of this review was to examine the effectiveness of personal protective measures in preventing pandemic influenza transmission in human populations. We collected primary studies from Medline, Embase, PubMed, Cochrane Library, CINAHL and grey literature. Where appropriate, random effects meta-analyses were conducted using inverse variance statistical calculations. Meta-analyses suggest that regular hand hygiene provided a significant protective effect (OR=0.62; 95% CI 0.52-0.73; I2=0%), and facemask use provided a non-significant protective effect (OR=0.53; 95% CI 0.16-1.71; I2=48%) against 2009 pandemic influenza infection. These interventions may therefore be effective at limiting transmission during future pandemics. PROSPERO Registration: 42016039896.
Keywords: Cough etiquette; Facemask; Hand hygiene; Pandemic influenza; Systematic review; Humans; Influenza, Human; Masks; Pandemics; Hand Disinfection